Research on Cold-Energy Loss of Long-Distance Sleeve-Type Insulated Pipe for High-Temperature Deep Mines - Lijuan Zhang; Wenlong Wang; Fengtian Yue; Jingsheng Wei; Tao Gao; Yangjie Wang; Yang Zhou (Energies)
As mining operations extend to greater depths, they encounter critical challenges, including increased distances and substantial energy losses. To address the challenges of cold-energy loss in deep mine cooling systems and improve the working environment for miners, a long-distance sleeve-type insulated pipe system was developed. This system aims to mitigate thermal energy loss caused by heat transfer between the pipe and surrounding soil throughout the water transport path from the source to the deep mine in boreholes. A heat transfer analysis model was developed to assess the impact of variables such as transport time, water flow rate, inlet temperature, and insulation materials on the temperature of cold water. The study reveals that the temperature of cold water increases rapidly during transportation before reaching a stable state. Implementing modifications such as increasing the inlet temperature, enhancing the water flow rate, or utilizing materials with lower thermal conductivity can effectively mitigate temperature rises. Additionally, the novel sleeve-type design enhanced the pipe’s pressure-bearing capacity, reduced the required pipe length by 4752 m and minimized energy loss compared to traditional systems. In practical applications, after 45 h, the supply and return water temperatures increased by 0.45 °C and 0.38 °C, respectively, while maintaining cooling energy loss below 12%. This innovative solution improves mine cooling efficiency and provides guidance to reduce cold-energy loss.